Analysis Risk Management Japanese Language Education Study Program Universitas Negeri Semarang - Fahrudin, Imam; Pramono, Suwito Eko; Widiyanto, Widiyanto (Educational Management, 2020)
The purpose of this study was to describe and analyze the risk management of the Japanese language education study program at Universitas Negeri Semarang. This research approach is a qualitative approach with a case study design. data collection using structured interview methods, unstructured interviews, and document study. The results of this study indicate that the risk management carried out by the Japanese language education study program Universitas Negeri Semarang is not yet structured, but is following the directions and rules of the university. Although not yet structured, risk management that is carried out can minimize the impact of a problem that can disrupt the stability or sustainability of the study program. There are already standard rules for handling each problem and special handling in each case. Carried out very carefully so that the stability of the study program is maintained. The benefit of this research is to provide insight into risk management in the Japanese language education program Universitas Negeri Semarang to maintain the quality of graduates and the sustainability of the study program itself and can be an example of risk management in other institutions.